2017
DOI: 10.2147/jn.s120173
|View full text |Cite
|
Sign up to set email alerts
|

Chromaffin cell transplantation for neuropathic pain after spinal cord injury: a report of two cases

Abstract: Neuropathic pain (NP), a common secondary complication following spinal cord injury (SCI), presenting at or below the level of injury is largely refractory to current pharmacological, physical, and surgical treatments. Previous studies have demonstrated the promising value of cell therapy including adrenal chromaffin cells that have the capacity to act as mini-pumps that release amines and peptides for alleviating chronic pain. The paper presents the cases of two gentlemen suffering from severe central NP afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A number of clinical studies concerning cell therapies with a positive outcome have led to the suggestion that combination cell therapies and/or certain transplantation approaches with rehabilitation can be more effective 107 , 123 , 128 130 , 136 , 138 …”
Section: Provisionsmentioning
confidence: 99%
“…A number of clinical studies concerning cell therapies with a positive outcome have led to the suggestion that combination cell therapies and/or certain transplantation approaches with rehabilitation can be more effective 107 , 123 , 128 130 , 136 , 138 …”
Section: Provisionsmentioning
confidence: 99%
“…0 represents extremely uncontrollable pain, one point represents severe pain that needs and responds to anesthetics, two points represents mild pain that responds to common painkillers, and three points represents no pain. The results showed that pain improved by an average of 1.2 points after OECs transplantation ( Chen et al, 2020 ). Another report is: a 72-year-old stroke patient with right limb sensory and functional impairment and pain for 8 years, 4-month fetal-derived OECs were transplanted into the patient’s brain (cell volume 1x10 10 /L -1 ).…”
Section: The Application Of Oecs In the Treatment Of Nppmentioning
confidence: 99%
“…Nowadays, a number of neurorestorative strategies have been brought to clinical practice, resulting in benefit to patients and improvement of their quality of life [[9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21]]. Given the rapid advances in the field, the International Association of Neurorestoratology (IANR) and the Chinese Association of Neurorestoratology (CANR) are working together to propose the improved vision of the “Clinical Neurorestorative Therapeutic Guidelines for Spinal Cord Injury (IANR/CANR version 2019)” based on the released guidelines [22].…”
Section: Introductionmentioning
confidence: 99%